Green synthesis of silver nanoparticles using extracts of Mikania cordata leaves and evaluation of their antioxidant, antimicrobial and cytotoxic properties - Monira Khatun; Ziasmin Khatun; Md. Rezaul Karim; Md. Rowshanul Habib; Md. Habibur Rahman; Md. Abdul Aziz (Food Chemistry Advances, 2023)
The synthesis of silver nanoparticles using plant extracts is a promising field of research due to the versatile biomedical application of metal nanoparticles. In the present study, silver nanoparticles (AgNPs) were synthesized using the aqueous extract of Mikania cordata leaves where extract act as both reducing and capping agents. Successful biosynthesis of AgNPs had been studied using UV Spectrophotometry that recorded the surface plasmonic resonance peak at around 451 nm. The structural properties and morphology of AgNPs were confirmed by scanning electron microscope with Energy dispersive X-ray (SEM/EDX), Fourier transform infrared (FT-IR) and X-ray diffraction (XRD) spectroscopic techniques. In antioxidant assays, AgNPs were found as strong free radical scavenger as ascorbic acid (standard) with the values of 10.06 (EC50, μg/mL) and 20.94 (EC50, μg/mL) for DPPH and ABTS radicals, respectively. In antimicrobial study, the effectiveness of synthesized AgNPs was observed as follows: Shigella boydii > Staphylococcus aureus > Shigella dysenteriae > Escherichia coli. Moreover, the results of cytotoxic assay indicated that AgNPs inhibited the growth of EAC cells in dose-dependent manner. Overall results of this study suggested that the synthesized AgNPs from Mikania cordata leaves have the merits to use in the field of nanomedicines.